Corporate governance perbankan syariah di Indonesia - Abdullah, Mal An, 1948- (Jogjakarta : Ar-Ruzz Media : Didistribusikan oleh Ar-Ruzz Media Group, 2010)
Implementation of good corporate governance in Islamic bankings in Indonesia.
Revision of the author's thesis (master's)--IAIN Raden Fatah, 2010.
Includes bibliographical references (p. 117-128).
Keywords: Banks and banking -- Indonesia -- Management; Banks and banking -- Religious aspects -- Islam; Corporate governance -- Indonesia; Corporate governance -- Religious aspects -- Islam